A novel endoplasmic stress mediator, Kelch domain containing 7B (KLHDC7B), increased Harakiri (HRK) in the SubAB-induced apoptosis signaling pathway - Kinnosuke Yahiro; Kohei Ogura; Hiroyasu Tsutsuki; Sunao Iyoda; Makoto Ohnishi; Joel Moss (Cell Death Discovery, 2021)
Abstract Locus for Enterocyte Effacement (LEE)-positive Shiga-toxigenic Escherichia coli (STEC) contributes to many global foodborne diseases, with infection characterized by severe gastrointestinal symptoms, including bloody diarrhea. The incidence of LEE-negative STEC-mediated disease is also increasing globally. Subtilase cytotoxin (SubAB) is released by some LEE-negative STEC strains. It cleaves BiP, which is a chaperone protein located in the endoplasmic reticulum (ER), thereby causing apoptosis induced by ER stress. To date, the apoptotic signaling pathway mediated by SubAB has not been identified. In the current study, RNA-seq analysis showed that SubAB significantly induced the expression of Kelch domain containing 7B (KLHDC7B). We explored the role of KLHDC7B in the SubAB-induced apoptotic pathway. SubAB-induced KLHDC7B mRNA expression was increased after 12 h of incubation of toxin with HeLa cells. KLHDC7B expression was downregulated by knockdown of PKR-like endoplasmic reticulum kinase (PERK), CEBP homologous protein (CHOP), activating transcription factor 4 (ATF4), and CEBP β (CEBPB). KLHDC7B knockdown suppressed SubAB-stimulated CHOP expression, poly(ADP-ribose) polymerase (PARP) cleavage, and cytotoxicity. The over-expressed KLHDC7B was localized to the nucleus and cytosolic fractions. Next, we used RNA-seq to analyze the effect of KLHDC7B knockdown on apoptosis induced by SubAB, and found that the gene encoding for the pro-apoptotic Bcl-2 family protein, Harakiri (HRK), was upregulated in SubAB-treated control cells. However, this effect was not observed in SubAB-treated KLHDC7B-knockdown cells. Therefore, we identified the pathway through which SubAB-induced KLHDC7B regulates HRK expression, which is essential for apoptosis in toxin-mediated ER stress.